Epidemiology of preinvasive lesions of the cervix and accuracy of its screening modalities in low resource settings - Rashi, Rashi; ., Shaheen; Rajyashri, Sharma; Zeepee, Godha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cervical cancer is the leading cause of deaths of women due to malignancies in developing countries worldwide. Having a latency period of upto10 years, preinvasive lesions of cervix give us a wide margin for detection and treatment before it becomes cancerous. This is the aim of this study is to establish a pattern of prevalence of these preinvasive lesions and find out correlation with various epidemiological factors and establish best screening modality in low resource settings like ours. Methods: The cases were studied in terms of their epidemiologic characteristics. The diagnostic accuracy of visual inspection with acetic acid (VIA) and cytology was assessed using colposcopy and biopsy as the gold standard, chi-square test applied and power of the screening test calculated. Results: Abnormal cytology (47/226) was mostly found in age group 30-40 29/47 (61.7%), were para 2 to 4 34/47 (72.3%), belonged to class IV-V socioeconomic class 28(59.6%), belonged to rural areas 32/47(68%) were illiterate 29/47(61.7%) were married at a young age 15-17 23/47(49%) and were not using any contraception 22/47(46.8%). The diagnostic accuracy of the screening tests that is VIA and cytology was tested against the gold standard test which was taken as colposcopy and biopsy in our study. Conclusions: VIA is a screening modality suitable for low resource setting like ours along with cytology. It also offers see and treat option for women in rural areas who are usually lost to follow up.